2020
DOI: 10.1093/nsr/nwaa231
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven directional ion transport for enhanced osmotic energy harvesting

Abstract: Light-driven ion (proton) transport is a crucial process both for photosynthesis of green plants and solar energy harvesting of some archaea. Here, we describe that TiO2/C3N4 semiconductor heterojunction nanotube membrane can realize a similar light-driven directional ion transport performance as biological systems. This heterojunction system can be fabricated by two simple deposition steps. Under unilateral illumination, TiO2/C3N4 heterojunction nanotube membrane can generate a photocurrent of about 9 μA/cm2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Xiao et al reported a C 3 N 4 /TiO 2 nanotube (CNTN) semiconductor heterojunction nanofluidic device that could realize a higher performance of light-driven directional ion transport than that of carbon nitride nanofluidics. 23 Under the same light illumination, the lightinduced ionic current could be enhanced to 9 μA/cm 2 , which could be ascribed to the more efficient photoinduced carrier separation.…”
Section: Photoelectric Effectmentioning
confidence: 92%
See 2 more Smart Citations
“…Xiao et al reported a C 3 N 4 /TiO 2 nanotube (CNTN) semiconductor heterojunction nanofluidic device that could realize a higher performance of light-driven directional ion transport than that of carbon nitride nanofluidics. 23 Under the same light illumination, the lightinduced ionic current could be enhanced to 9 μA/cm 2 , which could be ascribed to the more efficient photoinduced carrier separation.…”
Section: Photoelectric Effectmentioning
confidence: 92%
“…[15][16][17][18][19][20] Light-driven ion transport is an interesting phenomenon occurring in certain nanofluidic devices based on their material attributes. 8,[21][22][23] In these systems, the consumption of solar energy moves ions from a low concentration to a high concentration to establish a chemical potential (active transport) or amplify ionic flow from a high concentration to a low concentration (passive transport). The active ion transport phenomenon is common in microorganisms or green plants that pump protons or ions across cell membranes, generating an osmotic and charge imbalance via solar energy consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar strategies have been reported in 2D MXene membranes and TiO 2 /C 3 N 4 heterojunction nanotubes. 202,203 These examples illustrate the possibility to combine solar energy and SGE with a relatively simple strategy.…”
Section: Surface Charge Density and Locationmentioning
confidence: 99%
“…The bio-light driven ion pump uses the concentration gradient of ions to create a membrane potential [23], and converts the energy stored in sunlight into an osmotic potential. The application of nanochannels to participate in the photoelectric conversion process, directly or indirectly, has received increasing attention [24,79,217,218 [79] used PSII complexes extracted from green plants and certain bacteria, the natural photoelectric conversion materials, as a "pump" to convert light into ion current (Fig. 13a).…”
Section: Photoelectric Conversionmentioning
confidence: 99%